Matching provision to needs : the example of victim support - Simmonds, Lesley Anne (2004)
Merged with duplicate record (10026.1/682) on 03.01.2017 by CS (TIS)This is a digitised version of a thesis that was deposited in the University Library. If you are the author please contact PEARL Admin (pearladminplymouth.ac.uk) to discuss options.The current study is an evaluation of a voluntary sector service, Victim Support. The focal points of this work are the impact of crime upon victims and the extent to which they feel that Victim Support, as a service provider, has helped to restore their sense of equilibrium. In this way the success of a community response to crime is considered. The research was undertaken between 1998 and 2002 and was largely based upon the work of one local scheme; Victim Support, Plymouth. The study included the views of service users (victims of crime) and those of service providers (paid staff and volunteers). In contrast to earlier studies, my work looks at Victim Support at a much later date in its history, at a time when service provision has become increasingly professionalised and standardised. Furthermore my work examined Victim Support at a time when it is being charged, fairly overtly, with responsibilities alongside other voluntary and state agencies for the governance of crime. At the same time Victim Support is under pressure to provide a service that IS 'community' In nature, whilst meeting the stricter economic imperatives of managerialism. Previous studies do not appear to have considered the value of all types of service provision that Victim Support makes, nor have they directly included victims who, though quite badly affected, were not typically offered assistance. More recent studies of Victim Support have also been undertaken more as a by product of national victim surveys, with only vague references to the contact made with victims, and within which support is offered/provided. The work that I have undertaken seeks to address these gaps in knowledge, making a clear link between the needs of crime victims and the organisational response of Victim Support at the local level.Department of Social Policy and Social Work (as was) within the University of Plymout